The Effect Of Work Motivation And Job Satisfaction On Employee Performance at PT. Duta Karya Bersatu Surabaya. - Rohmatillah, Muhammad Fatih; Samsudin, Acep (Socious Journal, 2025)
This research seeks to investigate the relationships between employee performance (Y), job satisfaction (X2), and work motivation (X1) at PT. Duta Karya Bersatu Surabaya. A quantitative approach was taken in this investigation. The saturated sampling technique, which involves collecting samples from 30 individuals, is applied to the population, which consists of all PT. Duta Karya Bersatu Surabaya personnel. The findings of multiple linear regression analysis demonstrated that work motivation (X1) and job satisfaction (X2), both alone and in combination, had a substantial influence on employee performance (Y). The study's findings demonstrated a strong and favorable correlation between worker performance (Y), job satisfaction (X2), and employee motivation (X1). In addition, work motivation (X1) and job satisfaction (X2) have a good and significant influence on employee performance (Y) at PT. Duta Karya Bersatu Surabaya.